FOREWORD to Dimaras Lecture 2016 - Nikolaidis, Efthymios (The Historical Review/La Revue Historique, 2019)
We are very honoured that Prof Brooke has accepted to give the 2016 C. Th. Dimaras Lecture within the framework of his collaboration with the SOW project.